The Tradition Of Commemorating Fatima In Shia Communities Of Bukhara - Nigʻmatullayev Ibrohim Ma’ruf o‘g‘li (Periodica Journal, 2024)
The article gives information as to the tradition of commemorating Fatima in Bukhara Shia communities. In addition to this, “Fatima Ashura” - special features of the commemoration ceremony of Fatima and the role of the figure of Fatima, the daughter of the Prophet Muhammad (p.b.u.h.) in the rituals held among the women of the Bukhara oasis were researched in this article
Keywords: Fatima; rituals; women; Bukhara